PERAN ORANGTUA DALAM PENGGUNAAN GADGET DENGAN PERKEMBANGAN PSIKOSOSIAL DI MASA PANDEMI COVID-19 (Studi Pada Anak Prasekolah di TK Aisyiyah 9 Kabupaten Mojokerto) - Nisrina Marwa Rindani; Dwiharini Puspitaningsih; Fitria Wahyu Ariyanti (MEDICA MAJAPAHIT, 2024)
Using gadgets has become one of the basic needs of humans so that many negative impacts are caused by the use of gadgets because they cannot use gadgets well. One of the negative impacts caused by gadgets is the risk of psychosocial development problems. The purpose of the study was to determine the role of parents in the use of gadgets with psychosocial development in the Pandemic Covid-19 studies in preschool age children in TK Aisyiyah 9 Mojokerto Regency. This research design uses an analytical research design correlation with a cross sectional approach. The sampling used is simple random sampling so that 41 samples are obtained. This research instrument uses a questionnaire. Data analysis using the Spearman’s Rho test. The results showed that almost all respondents had a role in the use of gadgets in sufficient categories, namely 34 respondents (82.9%), almost all respondents had psychosocial development in the good category of 38 respondents (92.7%). Spearman's Rho test results show that Pvalue = 0.427 or more than α (0.05) which means there is no relationship between the role of parents in the use of gadgets with psychosocial development in the Pandemic Covid-19 period in TK Aisyiyah 9 Mojokerto Regency. Parents who have an adequate role turned out to be their children having good psychosocial development, this can be caused by the child's psychosocial development influenced by many factors, not only the role of parents in the use of gadgets. It is hoped that parents to limit the use of gadgets in children, which is a maximum of 2 hours a day, provide games and invite children to play with parents so that children do not always use gadgets.